Hubungan Lama Penggunaan KB Suntik Depo Medroxy Progesterone Acetat Dengan Gangguan Menstruasi Di BPM Rosalina Munthe Tahun 2025 - Diah Karlina; Ratih Widya Wati Gultom (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Injectable contraception is a type of hormonal contraceptive which is divided into two types, namely combined injection contraceptives and progestin injection contraceptives. One of the frequently used injectable contraceptives is the 3-month injectable contraceptive containing Depo-Provera (Depo Medroxy Progesterone Acetate). This contraceptive has good effectiveness, but has some side effects, such as menstrual disorders, weight gain, nausea, headaches, breast pain, and so on. Menstrual disorders that occur in the form of amenorrhea, hypermenorrhea, and spotting. Side effects that arise are the biggest cause of acceptors to stop using injectable contraceptives. A number of women complained that the use of contraceptive methods caused menstrual problems. However, it is hormonal in nature and not everyone experiences the same complaints. To find out " There is a long-standing relationship between the use of Depo Medroxy Progesterone Acetate KB injections and menstrual disorders at BPM Rosalina Munthe, in 2025. This type of research uses a cross sectional research design with chi square with a sampling technique that is total sampling. The results showed that the p-value of the relationship between DMPA injection duration and menstrual disorders was 0.03 <0.05. There is a long-standing relationship between the use of Depo Medroxy Progesterone Acetate KB Injections and Menstrual Disorders at BPM Rosalina Munthe, in 2025.